BERBAGAI PENANDA BIOLOGIS PADA URTIKARIA KRONIK SPONTAN (PERDOSKI, 2020)
Chronic spontaneous urticaria (CSU) is a mast cell driven skin disorder that is characterized by the development of recurrent itchy wheals for 6 weeks or more due to unknown causes. Diagnosis is purely clinical while assessment of disease activity, its impact on quality of life, as well as treatment efficacy are based on history, physical examination, and the use of questionnaires. However, questionnaires have the disadvantage of being subjective. In the last decade, studies have been focusing on understanding of chronic spontaneous urticarial pathomechanism and identification of potential biomarkers to determine disease activity, clinical course, and treatment efficacy. Some of the biomarkers that have been studied are D-dimer, C reactive protein, interleukin-6, FcεRI, and vitamin D. Biomarkers will then be classified into clinical and molecular biomarkers. With identification of biomarkers that considered to be more objective and reliable, personal approach in evaluating the course of the disease and the most suitable treatment for patients can be achieved.